A porous ultra-high channel ceramic material with high chemical stability and preparation method thereof
By using spherical β silicon carbide powder, boron carbide powder and water-soluble polyvinyl alcohol, combined with vacuum training and low-pressure extrusion molding, it is solved that porous ceramic materials are difficult in the plastic extrusion molding process. , The problem of poor chemical stability has achieved the preparation of porous ceramic materials with high chemical stability and thermal conductivity, and is suitable for a variety of application fields.
Patent Information
- Application Number
- CN202411545853.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-11-01
AI Technical Summary
The existing porous ceramic materials are difficult, have poor chemical stability, poor thermal conductivity, and have high cost and low efficiency in the plastic extrusion molding process.
Using spherical β silicon carbide powder, boron carbide powder, white sucrose, water-soluble polyvinyl alcohol (PVA) and other components, porous ultra-high channel ceramic materials are prepared through vacuum training and low-pressure extrusion molding to improve ceramics chemical stability and thermal conductivity.
The preparation of porous ultra-high channel ceramic materials with high chemical stability and high thermal conductivity has been achieved, which reduces the extrusion pressure, simplifies the production process, reduces costs, and increases the geometric specific surface area of the ceramics. It is suitable for medicine, environmental protection, etc. field.
Smart Images

Figure CN119039036B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of porous ceramic materials, and in particular to a porous ultra-high channel ceramic material with high chemical stability and a preparation method thereof. Background Art
[0002] Porous ceramics have the characteristics of ultra-high geometric surface area and are widely used. It can be used for contact and exchange between gas and gas, gas and liquid, gas and solid, and liquid and solid. With the development of new technologies and new energy sources, there is an increasing need for places with larger geometric surface areas for contact and exchange, such as various ultra-high channel microreactors used in the pharmaceutical industry, environmental protection, fuel cells, thermoacoustic refrigeration, thermoacoustic power generation, etc. In order to quickly carry out the temperature required for various physical and chemical reactions, it is hoped that the microreactor has a higher thermal conductivity and can quickly increase the temperature of the microreactor. At the same time, various gases and liquids may be highly corrosive. In order to ensure the service life of the ultra-high channel microreactor, it is necessary to improve the chemical stability of the microreactor and select dense reaction sintered silicon carbide material to prepare the microreactor.
[0003] Currently, the best method for preparing porous ceramics is to use plastic extrusion molding. However, as the pore density of porous ceramics increases and the wall thickness decreases, plastic extrusion becomes more and more difficult, the extrusion pressure required by the extrusion equipment increases rapidly, and the mud flow performance requirements become higher and higher. The current mass production capacity of silicon carbide porous ceramics prepared by plastic extrusion molding is 400cpsi, the wall thickness is 100μm, and the molding extrusion pressure has reached ≥20MPa.
[0004] At present, silicon carbide microreactors generally use 3D printing to manufacture ultra-high channel honeycomb ceramics. However, the preparation of microreactors by 3D printing is relatively complicated and costly. For example, in the patent CN116425548B, it is necessary to pre-3D print the ceramic blank, then degrease it, and then perform siliconization for densification. At the same time, since silicon metal is used for densification, silicon metal easily reacts with water vapor, strong alkali and strong acid, the chemical stability of the microreactor deteriorates, and there are also problems of high cost and low efficiency. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a porous ultra-high channel ceramic material with high chemical stability and a preparation method, so as to solve the problems of difficulty in plastic extrusion of porous ceramic materials, poor chemical stability, poor thermal conductivity, etc. in the prior art.
[0006] The technical solution of the present invention to solve the above technical problems is as follows:
[0007] The present invention provides a method for preparing a porous ultra-high channel ceramic material with high chemical stability, which is prepared by using a mud material; the mud material includes an inorganic solid component, the inorganic solid component includes a spherical β silicon carbide powder and a sintering aid, and the mud material also includes white sucrose, a binder, a lubricant and water; wherein the particle size D of the spherical β silicon carbide powder is 50 0.2-2.0μm, particle size D 100 The particle size of the spherical β silicon carbide powder is less than or equal to 10 μm, and the mass percentage of the β crystal phase in the spherical β silicon carbide powder is greater than or equal to 99.0%.
[0008] Based on the above technical solution, the present invention can also be improved as follows.
[0009] Furthermore, the sintering aid is boron carbide powder, and the particle size of the boron carbide powder is 50 0.1-1.0μm, particle size D 100 The boron carbide powder has a boron carbide content of 10 μm or less and a boron carbide content of 98.0% or more.
[0010] Furthermore, in the white sucrose, the mass percentage of water is less than or equal to 0.5%, and the mass percentage of water-insoluble matter is less than or equal to 0.5%.
[0011] Furthermore, the binder is a high-viscosity water-soluble polymer preparation, and the lubricant is a water-dispersible organic emulsion.
[0012] Furthermore, in the inorganic solid component, the mass percentage of each component is: the spherical β-silicon carbide powder is 99.0%-99.7%, and the sintering aid is 0.3%-1.0%; based on the mass of the inorganic solid component being 100%, the white sucrose is 2.0%-4.0%, the binder is 8.0%-12.0%, the lubricant is 6.0%-12.0%, and the water is 27%-32%.
[0013] Further, the following steps are included:
[0014] S1, mixing and stirring the spherical β-silicon carbide powder, the sintering aid, and the binder to obtain a powder;
[0015] S2, mixing the white sucrose with water to prepare a white sucrose solution, and wet-mixing and kneading the powder, the lubricant, and the white sucrose solution to obtain the mud material;
[0016] S3, refining the clay material under vacuum conditions to obtain a clay segment;
[0017] S4, extruding the mud segments and preparing them into a honeycomb structure, and then drying, cutting, sintering, and cold processing them in sequence to obtain the porous ultra-high channel ceramic material.
[0018] Further, in step S3, the vacuum degree of the vacuum condition is greater than or equal to -0.09 MPa.
[0019] Further, in step S4, the extrusion pressure is 8-12 MPa.
[0020] Furthermore, in step S4, the sintering temperature is 1700-1900° C., and the sintering holding time is 4-8 hours.
[0021] The present invention also provides a porous ultra-high channel ceramic material with high chemical stability, which is prepared by the above method; the porous ultra-high channel ceramic material has a pore density of 1000-60000 cpsi and a wall thickness of 1-2 mil.
[0022] The beneficial effects of the present invention are:
[0023] (1) The method for preparing the porous ultra-high channel ceramic material with high chemical stability of the present invention uses highly active spherical β-silicon carbide powder as the main raw material, which has high reactivity and can easily achieve densification by low-temperature sintering, thereby improving the ceramic packing density and mud fluidity and reducing the extrusion pressure;
[0024] (2) The method for preparing the porous ultra-high channel ceramic material with high chemical stability of the present invention comprises adding boron carbide as a sintering aid, lowering the sintering temperature, and densifying the silicon carbide ceramic;
[0025] (3) The method for preparing the porous ultra-high channel ceramic material with high chemical stability of the present invention uses water-soluble white sucrose as a molding aid to increase the viscosity and plasticity of the clay material, and is also beneficial to the sintering densification of silicon carbide ceramics;
[0026] (4) The method for preparing the porous ultra-high channel ceramic material with high chemical stability of the present invention uses water-soluble polyvinyl alcohol (PVA) without metal impurities as a binder to provide good lubricity and fluidity. At the same time, PVA is a pure organic polymer with no ash residue, which improves the chemical stability of the porous ceramic;
[0027] (5) The preparation method of the porous ultra-high channel ceramic material with high chemical stability of the present invention adopts the conventional plastic low-pressure (8-12MPa) extrusion molding preparation method to break through the technical barriers of high-pore density and ultra-thin-wall silicon carbide (silicon carbide content ≥96%) porous ceramics, and the production process is simple and the cost is low;
[0028] (6) The porous ultra-high channel ceramic material with high chemical stability of the present invention has the advantages of high pore density and thin wall, so that its geometric specific surface area is large to meet various needs;
[0029] (7) The porous ultra-high channel ceramic material with high chemical stability of the present invention can be widely used in the pharmaceutical industry, environmental protection, fuel cells, thermoacoustic refrigeration, thermoacoustic power generation, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a SEM image of spherical β-silicon carbide powder in the method for preparing a porous ultra-high channel ceramic material with high chemical stability of the present invention;
[0031] Figure 2 This is a SEM image of the porous ultra-high channel ceramic material prepared in Example 7 in the method for preparing the porous ultra-high channel ceramic material with high chemical stability of the present invention. DETAILED DESCRIPTION
[0032] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.
[0033] The method for preparing a porous ultra-high channel ceramic material with high chemical stability of the present invention adopts a mud material to prepare the material; the mud material includes an inorganic solid component, the inorganic solid component includes a spherical β silicon carbide powder and a sintering aid, and the mud material also includes white sucrose, a binder, a lubricant and water; wherein the D 50 0.2-2.0μm, D 100 The particle size is less than or equal to 10 μm, and the mass percentage of the β phase in the spherical β silicon carbide powder is greater than or equal to 99.0%.
[0034] The method for preparing a porous ultra-high channel ceramic material with high chemical stability of the present invention uses highly active spherical β-silicon carbide powder to give the porous ultra-high channel ceramic material high chemical stability and high thermal conductivity; at the same time, the highly active β-silicon carbide has high reaction activity and can easily achieve densification by low-temperature sintering. Figure 1 This is a microscopic morphology of spherical β silicon carbide powder in one embodiment of the present invention. The spheroidization of β silicon carbide raw materials can improve the ceramic packing density and mud fluidity and reduce the extrusion pressure. Water-soluble white sucrose is used as a molding aid. White sucrose is easily soluble in water. Long-chain polysaccharide molecules wrap inorganic raw material particles to form an organic molecule wrapping layer, which reduces the friction between inorganic raw material particles and increases the viscosity, plasticity and fluidity of the mud. At the same time, during the preparation process, argon is injected during sintering. Under the protection of argon, the long-chain white sucrose molecules are cracked to form nano-scale carbon. Nano-scale carbon is a sintering aid for silicon carbide and is beneficial to the sintering and densification of silicon carbide ceramics.
[0035] For the particle size of spherical β-SiC powder, its D 50 The finer the particle size, the higher the reactivity, the denser the silicon carbide ceramic, the better the chemical stability and the better the thermal conductivity. However, as D50 The smaller the particle size, the larger the specific surface area, the worse the powder fluidity, and the higher the extrusion pressure. The optimal range is set by combining the two requirements. At the same time, in order to ensure the extrusion of ultra-thin-wall ceramics and prevent coarse particles of raw materials from clogging the mold and forming appearance defects, it is necessary to control the maximum particle size D 100 .
[0036] Preferably, the sintering aid is boron carbide powder, and the D 50 0.1-1.0μm, D 100 The diameter of the boron carbide powder is less than or equal to 10 μm. The mass percentage of boron carbide in the boron carbide powder is greater than or equal to 98.0%. Using boron carbide as a sintering aid can promote the sintering of silicon carbide by reducing the grain boundary energy and increasing the surface energy, thereby reducing the sintering temperature and making the silicon carbide ceramics quickly densified. 50 The finer the particle size, the higher the sintering activity, the denser the silicon carbide ceramic, the better the chemical stability and the better the thermal conductivity. 50 The smaller the particle size, the larger the specific surface area, the worse the powder fluidity, and the higher the extrusion pressure. The optimal range is set by combining the two requirements. At the same time, in order to ensure the extrusion of ultra-thin-wall ceramics and prevent coarse particles of raw materials from clogging the mold and forming appearance defects, it is necessary to control the maximum particle size D 100 .
[0037] Preferably, in white sucrose, the mass percentage of water is less than or equal to 0.5%, and the mass percentage of water-insoluble matter is less than or equal to 0.5%.
[0038] Preferably, the binder is a high-viscosity water-soluble polymer preparation, and the lubricant is a water-dispersible organic emulsion.
[0039] Further preferably, the binder is water-soluble polyvinyl alcohol (PVA) without metal impurities. PVA is soluble in water, and PVA molecules can wrap the raw material particles to provide good lubricity and fluidity. At the same time, PVA is a pure organic polymer with no ash residue, which improves the chemical stability of the porous ceramic.
[0040] Further preferably, the lubricant is a nano-scale paraffin wax emulsion; the paraffin wax particles are nano-scale and can be filled between the raw material particles to play a lubricating role, improve the fluidity of the mud, and reduce the extrusion pressure. At the same time, after the paraffin wax emulsion is microwave dried, it can improve the drying strength of the green blank.
[0041] Preferably, in the inorganic solid component, the mass percentage of each component is: spherical β-silicon carbide powder 99.0%-99.7%, sintering aid 0.3%-1.0%; based on the mass of the inorganic solid component as 100%, white sucrose is 2.0%-4.0%, binder is 8.0%-12.0%, lubricant is 6.0%-12.0%, and water is 27%-32%.
[0042] The preparation method of the present invention comprises the following steps:
[0043] S1. Spherical β-silicon carbide powder, sintering aid and binder are mixed and stirred to obtain powder. The mixing and stirring can be carried out using an inclined high-power mixer for 1 to 2 hours.
[0044] S2. Mix white sucrose and water to prepare a white sucrose solution, and wet-mix and knead the powder, lubricant, and white sucrose solution to obtain a paste.
[0045] The wet mixing and kneading can be carried out using a kneading machine for 60-90 minutes.
[0046] S3, vacuumizing the clay material through a clay refining machine and refining the clay material under vacuum conditions to obtain a clay segment with plasticity. The vacuum degree of the vacuum conditions is greater than or equal to -0.09 MPa.
[0047] S4, extruding the mud segments and preparing them into a honeycomb structure, and then drying, cutting, firing, and cold processing them in sequence to obtain a porous ultra-high channel ceramic material.
[0048] Preferably, the drying method is microwave drying.
[0049] Preferably, the extrusion pressure is 8-12 MPa.
[0050] Preferably, argon gas is filled during firing, the firing temperature is 1700-1900° C., and the firing insulation time is 4-8 hours.
[0051] The porous ultra-high channel ceramic material with high chemical stability of the present invention is prepared by the above method.
[0052] The porous ultra-high channel ceramic material with high chemical stability of the present invention has a pore density of 1000-60000 cpsi, a wall thickness of 1-2 mil, and a geometric specific surface area of 48.22 cm 2 / cm 3 -291.26cm 2 / cm 3 .
[0053] The porous ultra-high channel ceramic material with high chemical stability of the present invention can be used to prepare various microreactors with ultra-high geometric specific surface areas, such as in the pharmaceutical industry, environmental protection, fuel cells, thermoacoustic refrigeration, thermoacoustic power generation, etc. The device of these ceramic materials has a diameter of 1-13 inches and a height of 2-12 inches.
[0054] There is no particular restriction on the shape of the honeycomb grid in the honeycomb structure. A single hole shape such as triangle, square, hexagon, etc. can be used, or multiple hole shapes such as square, hexagon, asymmetric, etc. can be used. It is not necessary to use a single hole shape in the honeycomb structure, and it is preferred to use, for example, square holes.
[0055] The present invention is illustrated below by means of specific examples.
[0056] Examples 1 to 9 are porous ultra-high channel ceramic materials prepared by the method of the present invention. Table 1 shows the property parameters of spherical β silicon carbide powder and boron carbide used in each example. The spherical β silicon carbide powder specifically includes spherical β silicon carbide powder T1, spherical β silicon carbide powder T2 and spherical β silicon carbide powder T3, and the boron carbide specifically includes boron carbide B1, boron carbide B2 and boron carbide B3. The comparative example uses a ceramic material prepared from 99.5% 1μm irregular ɑ silicon carbide, 0.5% boron carbide, 12% high viscosity (6000-10000mPa.s) HPMC, and 12% soybean oil or tung oil.
[0057] Table 2 shows the mass percentages of specific components in each embodiment. Taking the mass of spherical β-silicon carbide powder and boron carbide as 100%, the percentages of white sucrose, PVA, paraffin emulsion and water are the weight parts calculated in addition to the spherical β-silicon carbide powder and boron carbide.
[0058] The morphology of the porous ultra-high channel ceramic material prepared in Example 7 is as follows Figure 2 Table 3 is a comparison of the material properties of Examples 1 to 9 and the comparative example.
[0059] Table 1 Properties of spherical β-silicon carbide powder and boron carbide
[0060]
[0061] Table 2 Mass percentage of specific components in each embodiment
[0062]
[0063] Table 3 Comparison of material properties of Examples 1 to 9 and Comparative Examples
[0064]
[0065] It can be seen from Table 3 that in Examples 1-9, as the amount of white cane sugar increases, the extrusion pressure decreases, and as the pore density increases, the wall thickness decreases, and the extrusion pressure increases, but all can meet the requirements of 8-12 MPa; as the pore density increases, the wall thickness decreases, and the extrusion qualified rate shows a downward trend, but all can reach more than 97.5%, which is much higher than 94.23% of the comparative example.
[0066] At the same time, with the increase of boron carbide content, the thermal conductivity of porous ceramics shows a downward trend, but the thermal conductivity can reach above 82.4 W / m·K, which is much higher than 70.02 W / m·K of the comparative example. The reason for the difference is that the embodiment adopts highly active spherical β-silicon carbide powder, which is conducive to the densification of ceramics; with the increase of the amount of white sucrose added, the acid and alkali resistance of silicon carbide ceramics gradually improves. The reason is that the nanocarbon formed by the decomposition of white sucrose has high activity and can form silicon carbide and aluminum carbide with metal impurity ions such as Si and Al in silicon carbide, thereby improving chemical stability.
[0067] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a porous ultra-high channel ceramic material with high chemical stability, characterized in that: The clay material is prepared by using a clay material; the clay material includes an inorganic solid component, the inorganic solid component includes spherical β silicon carbide powder and a sintering aid, and the clay material also includes white sucrose, a binder, a lubricant and water; The particle size D of the spherical β silicon carbide powder 50 0.2-2.0μm, particle size D 100 Less than or equal to 10 μm, in the spherical β silicon carbide powder, the mass percentage of β crystal phase is greater than or equal to 99.0%; The sintering aid is boron carbide powder, and the particle size of the boron carbide powder is 50 0.1-1.0μm, particle size D 100 Less than or equal to 10 μm, the mass percentage of boron carbide in the boron carbide powder is greater than or equal to 98.0%; In the inorganic solid component, the mass percentage of each component is: the spherical β-silicon carbide powder is 99.0%-99.7%, the sintering aid is 0.3%-1.0%; based on the mass of the inorganic solid component being 100%, the white sucrose is 2.0%-4.0%, the binder is 8.0%-12.0%, the lubricant is 6.0%-12.0%, and the water is 27%-32%; The preparation method comprises the following steps: S1, mixing and stirring the spherical β silicon carbide powder, the sintering aid, and the binder to obtain a powder; S2, mixing the white sucrose with water to prepare a white sucrose solution, and wet-mixing and kneading the powder, the lubricant, and the white sucrose solution to obtain the mud material; S3, refining the clay material under vacuum conditions to obtain a clay segment; S4, extruding the mud segment and preparing it into a honeycomb structure, and then drying, cutting, sintering, and cold processing in sequence to obtain the porous ultra-high channel ceramic material; In step S4, the sintering is performed in an argon environment, the sintering temperature is 1700-1900° C., and the sintering holding time is 4-8 hours; The porous ultra-high channel ceramic material has a pore density of 1000-60000 cpsi and a wall thickness of 1-2 mil.
2. The method for preparing a porous ultra-high channel ceramic material with high chemical stability according to claim 1, characterized in that: The binder is a high-viscosity water-soluble polymer preparation, and the lubricant is a water-dispersible organic emulsion.
3. The method for preparing a porous ultra-high channel ceramic material with high chemical stability according to claim 2, characterized in that: In the white sucrose, the mass percentage of water is less than or equal to 0.5%, and the mass percentage of water-insoluble matter is less than or equal to 0.5%.
4. The method for preparing a porous ultra-high channel ceramic material with high chemical stability according to claim 1, characterized in that: In step S3, the vacuum degree of the vacuum condition is greater than or equal to -0.09 MPa.
5. The method for preparing a porous ultra-high channel ceramic material with high chemical stability according to claim 1, characterized in that: In step S4, the extrusion pressure is 8-12 MPa.
6. A porous ultra-high channel ceramic material with high chemical stability, characterized in that: The method is prepared by any one of claims 1 to 5.
Citation Information
Patent Citations
A binder jet printing silicon carbide ceramic composite material based on particle grading powder and a preparation method thereof
CN116425548B
Preparation method for silicon carbide ceramic tube or rod
CN101560104A
Silicon carbide / graphene bionic composite material for bulletproof armor and preparation method thereof
CN111825459A